Blunted glucagon but not epinephrine responses to hypoglycemia occurs in youth with less than 1 yr duration of type 1 diabetes mellitus. Issue 2 (28th August 2013) - Arbelaez, Ana Maria; Xing, Dongyuan; Cryer, Philip E; Kollman, Craig; Beck, Roy W; Sherr, Jennifer; Ruedy, Katrina J; Tamborlane, William V; Mauras, Nelly; Tsalikian, Eva; Wilson, Darrell M; White, Neil H; et al.
Abstract Context Glycemic control is limited by the barrier of hypoglycemia. Recurrent hypoglycemia impairs counterregulatory (CR) hormone responses to subsequent hypoglycemia. Objective To determine the glucagon and epinephrine responses to insulin‐induced hypoglycemia in adolescents with recent‐onset type 1 diabetes mellitus (T1DM). Methods We assessed the CR responses to hypoglycemia by performing a hyperinsulinemic (2.0 mU/kg/min), euglycemic (BG 90 mg/dL; 5.0 mmol/L)‐hypoglycemic (BG 55 mg/dL; 3.0 mmol/L) clamp in 25 recent‐onset (<1 yr duration) patients 9–18 yr old (mean ± SD: 13.4 ± 2.7) with T1DM and 16 non‐diabetic controls 19–25 yr old (mean ± SD 23.3 ± 1.8). Twenty of the T1DM subjects were retested 1‐yr (53 ± 3 wk) later. Results At the initial and 1‐yr studies, peak glucagon (pGON) and incremental glucagon (ΔGON) during hypoglycemia were lower in the T1DM subjects [median pGON = 47 pg/mL (quartiles: 34, 72), ΔGON = 16 (4, 27) initially and pGON = 50 pg/mL (42, 70), ΔGON = 12 (9, 19) at 1‐yr] than in controls [pGON = 93 pg/mL (60, 111); ΔGON = 38 pg/mL (19, 66), p = 0.01 and p = 0.004 for ΔGON at initial and 1‐yr study, respectively]. In contrast, peak epinephrine (pEPI) and incremental epinephrine (ΔEPI) levels were similar in the T1DM (pEPI = 356 pg/mL (174, 797) and ΔEPI = 322 pg/mL (143, 781) initially and pEPI = 469 pg/mL (305, 595) and ΔEPI = 440 pg/mL (285, 574) at 1 yr) and in controls (pEPI = 383 pg/mL (329, 493) and ΔEPI = 336 pg/mL (298, 471) p = 0.97 and 0.21 for ΔEPI at initial and 1‐yr study, respectively). Conclusions Even within the first year of T1DM, glucagon responses to hypoglycemia are blunted but epinephrine responses are not, suggesting that the mechanisms involved in the loss of these hormonal responses, which are key components in pathophysiology of hypoglycemia‐associated autonomic failure, are different.